Migration Policy in the Canary Islands: Human Rights Violations During the Pandemic - Rodríguez Salinas, Roberto (2022)
Irregular migration is a complex phenomenon that defies the sole concepts of movement restriction and lockdown introduced by the pandemic. Accordingly, 2020 was a particularly tense year for migratory fluxes from Africa to Europe. The Canary islands route saw a reactivation after almost a decade of low activity, with 23,023 registered arrivals in 2020. Similarly to other European islands, such as Lesbos or Lampedusa, the Canary islands have limited state assistance resources for immigrants. The pandemic is, thus, a cause of the massive emigration in the Maghreb and Sub-Saharan Africa, but is also a decisive factor for the human rights violations before, during and after the immigrants’ arrival at the islands. Under these circumstances, Spain is obliged to comply with international, European, and national law regarding migrants’ fundamental rights. This paper argues that Spain must always guarantee the health protection of refugees and asylum seekers during the legal procedures of intervention, assistance and detention. Furthermore, the enforcement of sanitary measures is not a valid cause for omitting certain guarantees such as the right to legal assistance, the freedom of movement within national territory, the compliance with detention times, and the use of clean and safe reception centers.